Control and Navigation of Differential Drive Mobile Robot with PID and Hector SLAM: Simulation and Implementation - Fahmizal Fahmizal; Matthew Sebastian Pratikno; Hidayat Nur Isnianto; Afrizal Mayub; Hari Maghfiroh; Pinto Anugrah (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2024)
Navigation technology is essential in fields like transportation and logistics, where precise mapping and localization are critical. Simultaneous Localization and Mapping (SLAM) technologies, such as Hector SLAM, enable robots to map environments by detecting and predicting object locations using sensors like LiDAR. Unlike other SLAM methods, Hector SLAM operates without odometry, relying solely on LiDAR data to produce accurate maps. This study investigates the application of Hector SLAM in a differential drive mobile robot controlled via the Robot Operating System (ROS), with PID control managing the motor speeds. The research contribution is the integration of Hector SLAM with PID control to enhance mapping accuracy in environments without odometry data. The method involves testing the robot's mapping performance in an indoor environment, focusing on the impact of varying linear and angular velocities on the quality of the generated maps. The PID control was tuned to ensure stable speed values for the robot's differential drive motors. Results show that Hector SLAM, when combined with well-tuned PID control, generates highly accurate maps that closely match the actual environment dimensions, with minimal errors. Specifically, the mapping error was found to be within 0.10 meters, validating the effectiveness of this approach in non-odometric systems. In conclusion, the study demonstrates that Hector SLAM, supported by PID-controlled motor stability, is an effective solution for mapping in differential drive mobile robots, particularly in scenarios where odometry is unavailable.